The central role of tRNA in genetic code expansion - Reynolds, Noah M.; Vargas-Rodriguez, Oscar; Söll, Dieter; Crnković, Ana (Biochimica et biophysica acta, 2017)
The development of orthogonal translation systems (OTSs) for genetic code expansion (GCE) has allowed for the incorporation of a diverse array of non-canonical amino acids (ncAA) into proteins. Transfer RNA, the central molecule in the translation of the genetic message into proteins, plays a significant role in the efficiency of ncAA incorporation. Here we review the biochemical basis of OTSs for genetic code expansion. We focus on the role of tRNA and discuss strategies used to engineer tRNA for the improvement of ncAA incorporation into proteins. The engineering of orthogonal tRNAs for GCE has significantly improved the incorporation of ncAAs. However, there are numerous unintended consequences of orthogonal tRNA engineering that cannot be predicted ab initio. Genetic code expansion has allowed for the incorporation of a great diversity of ncAAs and novel chemistries into proteins, making significant contributions to our understanding of biological molecules and interactions. This article is part of a Special Issue entitled “Biochemistry of Synthetic Biology - Recent Developments” Guest Editor: Dr. Ilka Heinemann and Dr. Patrick O'Donoghue. [Display omitted] •Transfer RNA is the central molecule in the translation of nucleic acid into protein.•Engineering of orthogonal tRNA (o-tRNA) interactions with host translational machinery aids genetic code expansion (GCE).•There are many unexpected outcomes of o-tRNA engineering.•Full orthogonality of tRNAs devoted to GCE is vital for cellular fitness.